The Research of Two Sugarcane Variety (Saccharum officinarum ) as The Raw Materials of Bioethanol Production in Negara Bumi Ilir - Lampung - M.C. Tri Atmodjo; Agus Eko T; Sigit Setiadi; Nurul Rusdi; Ngatinem JP; . Rina; . Melina; Agus Himawan (Bandar Lampung University (UBL), 2012)
This research was conducted in order to find out which sugarcane is better between GMP2 and Kidang Kencana as the raw material for bioethanol production by the application of organic and chemical fertilizer for the plant growth regulator. Four treatment with 3 replication was done that V1P1 was Kidang Kencana with organic fertilizer, V1P0 was Kidang Kencana wthout organic fertilizer, V2P1 was GMP2 with organic fertilizer and V2P0 was GMP2 without organic fertilizer. The application of green manure got better plant growth, total sugar and juice volume. GMP 2 seemed better than Kidang Kencana as the raw material for bioethanol production